A practical approach to identifying and prioritizing modernization of legacy systems - Ortiz-Ochoa, Mauricio (2016)
Currently, there are information systems that were created decades ago but are still being used, thus, today such technology is considered obsolete. In this regard, new requirements, changes or improvements are more expensive because those systems are still playing a significant role in organizations and therefore need maintenance. This paper presents a basic process that enables us objectively identifying software assets in the organization, categorize different systems as legacy and finally prioritize modernization through four levels of action called: remove application, normal maintenance, conditional maintenance and modernization.